Bounded Rationality in Energy Policy: Analyzing the Ban on Retail Sales of Subsidized 3-Kilogram LPG in Indonesia - Siahaan, Sonia Trifosa; Laudie, Gege; Siringo-ringo, Angel Icha Leony; Salsabila, Diva Nayla; Aryanisah, Bintang; Ghufran, Fawwaz (Center for Maritime Policy Governance Studies (CMPGS), 2025)
The prohibition of retail sales of subsidized 3-kilogram Liquefied Petroleum Gas (LPG) in Indonesia represents the government’s effort to improve subsidy distribution efficiency and prevent misuse by non-eligible consumers. However, this study argues that the formulation and implementation of the policy reflect the phenomenon of bounded rationality in public decision-making. The purpose of this research is to analyze how cognitive, informational, and temporal limitations affected the design and execution of the policy, resulting in deviations from its intended objectives. Using a qualitative descriptive approach and literature review method, this study examines secondary data from academic journals, official reports, and credible media sources to understand the dynamics of policy implementation. The findings reveal that the policy, while aiming to ensure accuracy in subsidy targeting, inadvertently restricted access for low-income households and small traders, leading to economic strain and the emergence of black markets. Weak data verification, limited public communication, and poor monitoring further exacerbated implementation challenges. Viewed through the lens of bounded rationality, policymakers acted under fiscal and political pressure, opting for “satisficing” solutions instead of optimal decisions. The study concludes that future energy subsidy reforms must integrate digital data systems, enhance beneficiary verification, and strengthen participatory oversight to minimize irrational policy outcomes and ensure equitable energy access for vulnerable communities.